การประยุกต์ยานยนต์ไฟฟ้าสำหรับบริการเสริมการควบคุมความถี่ในระบบไฟฟ้า - ประพันธ์ ถาไชย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
According to the increase of the charging stations, the policy, the development of battery and cost reductions, the number of global electric passenger cars has recently reached 3 million in 2017. From a significant increase in electric vehicles (EV), the concept of using the EV for an ancillary service in the power system is discussed. Regarding the ancillary service in the power system, there are 4 functions, i.e. frequency regulation, peak power shaving, reactive power compensation, and renewable energy support. Among those 4 functions, the frequency regulation is focused in this paper, since the frequency is a power system state variable. In this research, the application of EV as the frequency regulation service is focused on secondary control (SC). Because the regulation period of SC is a suitable range for the owner or aggregator to decide for entering the service. To validate the proposed concept, the EV model is tested in the distribution system with 2 cases, namely aggregated mode and distributed mode. Form the simulation result, it was found that convergence of the frequency response and overall power system stability are better.